Remington's Pharmaceutical Sciences (Nack, 1990)
Contents of this book include: Orientation; Pharmaceutics; harmaceutical Chemistry; Testing and analysis; Radioisotopes in pharmacy and medicine; Phrmaceutical and medicical Agents; Biological products and Pharmaceutical practice.